Mainstreaming climate adaptation and mitigation policy: towards multi-level climate governance in Melaka, Malaysia - Zen, Irina Safitri; Al-Amin, Abul Quasem; Doberstein, Brent (Elsevier BV, 2019)
Cities' responses to the challenge of climate change mainly relate to urban spatial planning and capacity-building initiatives. Those are enhanced by supportive climate adaptation policies at the sub-national level, which open up potential benefits and opportunities. Using the city of Melaka as a case study, this paper examines the importance of supportive climate adaptation policies using ‘good practices’ within a multi-level climate governance framework. This framework is evaluated by horizontal and vertical dimensions which assess policy actions designed to close the gap between national and local levels. Melaka is aiming to become a greener city, and its carbon reduction target is intended to support climate mitigation. This is discussed in relation to dynamic horizontal and vertical interactions at various scales. This study also examined why Melaka is considered a testing ground for climate mitigation projects that may subsequently be applied in other Malaysian states. A dual, collaborative, top-down and bottom-up approach and likely ways forward are also discussed as elements of good multi-level governance. The findings of this study should inform the application of multi-level governance in other states in Malaysia and elsewhere with similar ecological and economic contexts.